2005
DOI: 10.1088/0953-2048/18/3/026
|View full text |Cite
|
Sign up to set email alerts
|

Properties of helical springs used to measure the axial strain dependence of the critical current density in superconducting wires

Abstract: The use of helical (Walters) springs is an effective technique for measuring the critical current density (J C ) of superconducting wires in high fields as a function of both compressive and tensile axial strains. We report J C versus strain measurements for Nb 3 Sn wires on a number of helical springs of different materials and geometries, together with results from finite element analysis (FEA) of these systems. The critical current density, n-value and effective upper critical field data are universal funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…The thermal coefficient of linear expansion for Ti alloys is similar to the intermetallic superconductor Nb3Sn (i.e. 7.6 10 -6 K -1 ), but of course in practice, the thermal properties of a Ti alloy and a composite Nb3Sn strand, which includes softer materials such as copper that bring higher thermal contraction coefficients, are not perfectly matched [17]. We sort a barrel material with similar thermal and mechanical properties to Ti-64 but with a lower critical temperature.…”
Section: Materials and Measurementsmentioning
confidence: 99%
“…The thermal coefficient of linear expansion for Ti alloys is similar to the intermetallic superconductor Nb3Sn (i.e. 7.6 10 -6 K -1 ), but of course in practice, the thermal properties of a Ti alloy and a composite Nb3Sn strand, which includes softer materials such as copper that bring higher thermal contraction coefficients, are not perfectly matched [17]. We sort a barrel material with similar thermal and mechanical properties to Ti-64 but with a lower critical temperature.…”
Section: Materials and Measurementsmentioning
confidence: 99%
“…The is taken from the susceptibility-temperature measurement of this wire that was made in a magnetometer. Using the same parameters as that used to fit the Ti-alloy barrel measurements, the measured on other barrels are fit by only changing the strain coefficient [1]. In fitting the data, the self-field generated by the transport current is taken into account.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Various materials have been tried in the past including copper, stainless steel, Inconel 600, and fiberglass reinforced plastics like G-10 or G-11. In 2005, Taylor of ITER-type wires using helical springs of different materials [1]. They used Ti-6Al-4V alloy, Cu-Be (copper-beryllium), brass and 316 L stainless steel as spring material, and showed that the change in behavior of the wire in the different springs is solely due to a change in the thermal pre-strain in the wire which depends on the thermal contraction of the spring material.…”
Section: Introductionmentioning
confidence: 99%
“…Many facilities already offer precise and thorough measurement of performances versus axial strain (helical spring [1], pacman spring [2]), bending strain (tarsis probe [3]) or contact stresses (tarsis contact stresses [4]). Our idea was to develop a setup able to test a strand in bending conditions in the limited space required for a VAMAS sampleholder.…”
Section: A General Conceptmentioning
confidence: 99%